2021
DOI: 10.1016/j.psj.2021.101370
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial resistance in chicken-source phylogroup F Escherichia coli: similar populations and resistance spectrums between E. coli recovered from chicken colibacillosis tissues and retail raw meats in Eastern China

Abstract: The extended-spectrum cephalosporin resistant E. coli from food animals transferring to community settings of humans causes a serious threat to public health. Unlike phylogroup B2 E. coli strains, the clinical significance of isolates in phylogroup F is not well revealed. Here, we report on a collection ( n = 563) of phylogroup F E. coli isolates recovered from chicken colibacillosis tissues and retail raw chicken meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
1
26
2
Order By: Relevance
“…Detection of phylogroup F may help predict highly virulent APEC. The zoonotic potential of phylogroup F E. coli in the present study may be clarified through further research on multilocus-sequence typing ( Zhuge et al, 2021 ) and antimicrobial resistance ( Wang et al, 2021 ) of the isolates.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Detection of phylogroup F may help predict highly virulent APEC. The zoonotic potential of phylogroup F E. coli in the present study may be clarified through further research on multilocus-sequence typing ( Zhuge et al, 2021 ) and antimicrobial resistance ( Wang et al, 2021 ) of the isolates.…”
Section: Discussionmentioning
confidence: 91%
“…APEC isolates obtained from diseased poultry occasionally belong to the phylogenetic group D in Thailand ( Thomrongsuwannakij et al, 2022 ) and groups A and D in Japan ( Asai et al , 2011 ; Ozaki et al, 2017 ), based on the original Clermont scheme. Recently, several studies focused on avian colibacillosis strains belonging to phylogroups B2 and F based on the revised Clermont scheme due to their zoonotic potential as an etiologic agent of extraintestinal infections in humans ( Jeong et al, 2021 ; Wang et al, 2021 ; Zhuge et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While group A is related to human commensal strains [ 32 ], strains from phylogroup D are associated with human infections which its high prevalence among APEC isolates is concerning [ 23 ]. Since the zoonotic risk of chicken-source phylogroup F E. coli and its contribution to spread of MDR E. coli to humans heve been proposed recently [ 33 , 34 ], the high portion of group F members should not be neglected. Moreover, the observed scattered distribution of APEC strains in different phylogroups may indirectly reflects the commensal nature of APEC strains who broken the host defence and ended up a septicemic infection [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under commercial conditions in Portugal, the overall 10-year antibiotic resistance of APEC strains is amoxicillin 78%, ampicillin 73.5%, tetracycline 63.3%, doxycycline 56.4%, apramycin 34.5%, neomycin 68.2%, flumequine 39.4%, cotrimoxazole 47.7%, florfenicol 46.6%, and lincospectin 66.3% (Oliveira et al, 2022). In China, the prevalence of extended-spectrum cephalosporinresistant strains in E. coli from chicken colibacillosis and raw meat separately accounted for 66.1% and 71.2% (Wang et al, 2021). Previous studies indicated that APEC strains found in poultry are shown to be important reservoirs for antibiotic resistance genes (Nandi et al, 2004).…”
Section: The Zoonotic Potential Of Avian Pathogenic Escherichia Coli ...mentioning
confidence: 99%